FATES OF BOOKS AND ARCHIVES DURING THE WAR BETWEEN FINLAND AND THE SOVIET UNION, 1939–1940 AND 1941–1944 - MÄKINEN, ILKKA (Knygotyra, 2015)
The article describes the fates of books and archives during the Second World War in the hostilities between Finland and the Soviet Union, especially during the second phase of hostilities, 1941–1944. During the Winter War (1939–1940) the Soviet troops invaded the Finnish Karelia a great quantity of Finnish books was left in the hands of the Soviet authorities. The most important libraries in the region, the Viipuri City Library with its architectonically outstanding building designed by Alvar Aalto and the city library of Sortavala remained on the Soviet side of the border. After Winter War the border was drawn as it is now, west of the city of Vyborg (Viipuri). During the second phase of the hostilities, 1941–1944 (which the Finns call the “Continuation War”), when Finland was fighting side by side with the Germans against the Soviet Union, Finnish troops took back the parts of the Finnish Karelia invaded by the Soviets during the Winter War, but after that they continued into the Soviet Karelia and took hold of large parts of the Soviet (or East) Karelia that had never been part of Finland. The biggest city captured was Petrozavodsk (or Petroskoi in Finnish). When the Finnish troops had taken control of East Karelia, they started to gather all material and information important for the conduct of war. Books and archives of the Soviet authorities but also individual people who had fled were collected in Petrozavodsk to be sorted and researched. A big library and archive was created, about one million books and over one kilometre of archival material. They were used for military intelligence, but there also was a great interest in the Finnish libraries, archives and other institutions to get books printed in the Soviet Karelia (and the Soviet Union in general) and important parts of the archives. There also was a plan to create a “Karelian Central Library and Archive” in Petrozavodsk that would operate still after the war. Among the archives that fell into the Finnish hands were, e.g., the personal files of the Baltic Sea–White Sea Canal workers. Some of the aspirations of the Finnish libraries were inspired by the concept of the NATIONAL literature: what belongs to the Finnish national literature, which is called “Fennica”. Fennica was understood of consisting of books in Finnish (and in the closest Finno-Ugric languages, such as Karelian), and books by Finnish authors in any language. Even books in Finnish published outside Finnish borders were considered belonging under the concept of Fennica, which means that even books in Finnish published in Soviet Karelia during the 1920s and 30s were part of Fennica. Many Finnish libraries collecting a complete Fennica collection were eager to obtain books from East Karelia. Large quantities of books and archives were transported into Finland from East Karelia, especially after the war seemed to turn badly for the Germans and the safety situation in East Karelia was considered risky. After the defeat in 1944 (when East Karelia had to be abandoned and Finnish Karelia was permanently lost) practically all archives and books were returned to the Soviet Union. A number, not yet examined, of the books were not returned. These books, most often modest publications, such as school text books, official publications, novels etc., were scattered in the stocks of the libraries or came there only after the war. They had in the first place a bibliographical value as specimens of the Fennica literature published in the Soviet Union, not much economic value.